Telaah Konsep Akad Mudharabah Di Indonesia (Tinjauan Pelaksanaan Akad Mudharabah Di Bank Syariah Indonesia) - Deni Rahmatillah; Nuryanti Nuryanti (ISLAMIC BUSINESS and FINANCE (IBF), 2021)
This journal is entitled “A Review of The Concept of Mudharabah Contracts in Indonesia (review of the implementation of the mudharabah contract at Bank Syariah Indonesia). This study uses a normative approach. The data were obtained through library research (library research). Data analysis was carried out qualitatively on all literature sources about the topic, namely research that seeks to collect data from the treasures of literature and make the world of text the main object of its analysis. Based on the research conducted, it is known that the Mudharabah contract carried out by Indonesian Islamic Banks still has some shortcomings in its implementation. Such as the pattern of profit sharing that is unclear and convoluted, because Islamic banks combine all funds so that it cannot be distinguished which customer funds have been channeled and which ones have not been distributed, as well as readiness to accept losses when the business fails, the bank and customers are not ready to take the consequences if the company run by the Mudharib suffers losses, and the banking position is not clear, when the Islamic Bank becomes Mudharib, in a short time the funds will be channeled back to the customer. At that moment, the position of the Islamic Bank has changed to Sahib al-Mal.Keywords: Concept, Mudharabah, Contracts, Indonesia